Exploring DNA Functionalization Techniques for Silver Nanoparticles - Sebastian Freko; Marta Nikić; Lennart J.K. Weiß; Bernhard Wolfrum (Advanced Materials Interfaces)
Abstract Metal nanoparticle‐based spherical nucleic acids (SNAs) have been widely used in various fields, such as imaging and biosensing. However, functionalizing nanoparticles with specific properties, such as high DNA density or the attachment of long oligonucleotides, can be challenging. Choosing the ideal strategy is essential, as each functionalization method yields distinct results and has its limitations. In this study, four functionalization techniques — salt‐aging, pH‐assisted, freezing‐directed, and microwave (MW)‐assisted methods are investigated — for modifying silver nanoparticles (AgNPs), focusing on thymine‐strands (T‐strands) of varying lengths. The resulting DNA‐AgNP conjugates are characterized using UV/Vis spectroscopy and dynamic light scattering (DLS), and colloidal stability and DNA loading are assessed. The reagent‐free freezing‐directed and MW‐assisted methods follow a straightforward implementation. Generally, they result in higher DNA loading than salt‐aging and pH‐assisted methods, particularly when functionalizing with longer strands. However, these methods require higher DNA excess for shorter strand lengths and thus cannot be used to synthesize conjugates with low DNA densities. The different properties of each functionalization method can be exploited to construct various AgNP‐based SNAs with distinct specifications. The findings provide a methodological user guide to facilitate the selection of the most suitable functionalization strategy, thereby extending their utility in various nanobiotechnological applications.